Does the hexosamine biosynthetic pathway play a role in mediating the beneficial effects of oleic acid in the heart? - Harris, E. R. (Eurinah Roberta) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.